Precipitation behaviour in AlMgZnCuAg crossover alloy with coarse and ultrafine grains - P. D. Willenshofer; M. A. Tunes; C. Kainz; O. Renk; T. M. Kremmer; S. Gneiger; P. J. Uggowitzer; S. Pogatscher (Materials Research Letters, 2023)
Crossover aluminium alloys have recently been introduced as a new class of coarse-grained age-hardenable alloys. Here, we study the evolution of precipitation of the T-phase — [Formula: see text]-phase — in a 5xxx/7xxx crossover alloy with coarse- and ultrafined microstructures. Both alloys were examined using differential scanning calorimetry, X-ray diffraction and in situ transmission electron microscopy. The ultrafine-grained alloy revealed significant different and accelerated precipitation behaviour due to grain boundaries acting as fast diffusion paths. Additionally, the ultrafine-grained alloy revealed high resistance to grain growth upon heating, an effect primarily attributed to inter-granular precipitation synergistically with trans-granular precipitation of T-phase.